A quinoxaline based N-heteroacene interfacial layer for efficient hole-injection in quantum dot light-emitting diodes. Issue 27 (19th June 2015) - Bai, Linyi; Yang, Xuyong; Ang, Chung Yen; Nguyen, Kim Truc; Ding, Tao; Bose, Purnandhu; Gao, Qiang; Mandal, Amal Kumar; Sun, Xiao Wei; Demir, Hilmi Volkan; Zhao, Yanli
Abstract : N-Heterocyclic quinoxalines as hole transport layer in quantum dot light-emitting diodes show a narrow bandgap. Abstract : A series of N-heterocyclic quinoxaline derivatives was successfully synthesized and applied as hole transport layers in quantum dot light-emitting diodes (QLEDs). By inducing sp 2 N-atoms into the quinoxaline backbone, the electron affinity of the obtained material was enhanced, and its optical properties and bandgap became tunable. Quinoxaline based N-heteroacenes show a narrow bandgap, high thermal stability, and aligned film morphology. The resulting N-heteroacene polymer based QLED exhibits superior performance to poly(9-vinylcarbazole) based QLED. This study presents a strategy towards the design of novel N-rich molecules for the fabrication of QLEDs with improved performance.